Primer on US Food and Nutrition Policy and Public Health: Marion Nestle Comments - Nestle, Marion (American journal of public health (1971), 2019)
The profound influence of food policies on public health is best illustrated by the vast number of people affected by these policies. All three of the most prevalent problems in worldwide public health-undernutrition, overnutrition, and climate change- have roots in dysfunctional food systems. Hunger and malnutrition affect more than 800 million people,1 more than two billion people are overweight and at risk for chronic disease,2 and all of us are subject to the impact of food production on climate change.3How the US food system affects public health is a matter ofintense current interest. "Food system" means the totality of processes through which food is produced, transported, sold, prepared, consumed, and wasted.4 Policies governing these processes emerged piecemeal over the past century in response to specific problems as they arose, with regulatory authority assigned to whatever agency seemed most appropriate at the time.5 Today, multiple federal agencies oversee food policies. For some policy areas, oversight is split among several agencies-the antithesis of a systems approach.